Erotical Riddles in Javanese and Indonesian - Wijana, I Dewa Putu (Universitas Dian Nuswantoro, 2022)
This article is about erotical riddles found in Javanese and Indonesian. By using data collected and formulated through an introspective method, it is found that the addressers commonly construct erotic riddles in odd interrogative sentence types intended to deceive and mislead the addressees. The riddled topics are mostly about human genital and everything related to it, woman's breasts, and sexual activity. The humorous riddle discourses are created by various riddling techniques, such as analogy and metaphor, homonymy, sound change, word and syllabic permutation, and metonymy. Javanese and Indonesian erotic riddle discourses often contain code-mixing of the two codes mastered almost equally well by the bilingual interlocutors living in bilingual and diglossic speech communities.